Perhitungan Nilai OEE Efektivitas Mesin Produksi Cup Menggunakan Metode Overall Equipment Effectiveness (OEE) - Faisol, M Amir; Hamidah, Nur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to calculate the OEE (Overall Equipment Effectiveness) value as a measure of machine efficiency in the cup production process. OEE is an important parameter in evaluating machine performance, which includes three main factors, namely availability, performance, and quality. By using the OEE method, this study will analyze the effectiveness of cup production machines in a manufacturing industry. The data used include machine operating time, the number of products produced, and the number of defective products that occur during the production process. The results of the OEE calculation show the level of machine effectiveness that can be used to identify areas that require improvement. With optimal OEE results, companies can increase production efficiency, reduce downtime, and improve product quality. defects every production time.